A systematic review of obesity as a barrier to accessing cancer screening services. (27th April 2022) - Graham, Yitka; Hayes, Catherine; Cox, Julie; Mahawar, Kamal; Fox, Ann; Yemm, Heather
Abstract: Introduction: Obesity is a known risk factor for the development of cancers, and a significant proportion of the population may be at risk of developing cancer owing to their weight status. There is acknowledged societal stigma towards people living with obesity, which can influence health behaviors and deter help seeking, such as cancer screening. Healthcare professionals' attitudes and views toward people living with obesity may adversely affect the patient–professional interface and treatment. Methods: A systematic review was carried out which aimed to explore the impact of living with obesity on the uptake of three main cancer‐screening services: breast, cervical, and colorectal. Results: Ten studies were included in the review. Three main areas were identified from both a patient and healthcare professional perspective: barriers and challenges to screening, gender issues, and disparities in the population living with obesity. Conclusion: Further research is needed to improve uptake of cancer screening services, and for education on weight bias, which is often unconscious, to be considered for healthcare professionals working in cancer screening services. This may help to increase the incidence of early differential diagnosis of potential cancers and improve health outcomes for people living with obesity.